'It's literature I want, Ivo, literature!' Literature as screenplay as literature. Or, how to win a literary prize writing a screenplay. (1st March 2014) - Geerts, Ronald
Ivo Michiels, besides being one of the most acclaimed and radical experimental literary authors in Dutch literature, is arguably the first Flemish professional screenwriter.These two occupations, that he continuously tried to combine, resulted in screenplays that either have been published as novels (and awarded important literary prizes) or repurposed as fragments in the Journal Brut cycle. Michiels developed a specific style for the screenplay by turning away from economical concrete descriptions. Instead he pursued a more literary way of writing, using narrative strategies aiming at certain effects in the mind of the reader, over conventional description. This article situates Michiels' script writing as 'performative' in its intention and offers a case study of his work, as an expanded notion of the screenplay that elevates the form beyond mere description of what will be visible/audible on-screen. In Michiels' practice, a screenplay is not just a text that 'desires to become another text', in the words of Pier Paolo Pasolini. In contrast, this article frames Michiels' screenplays as 'postdramatic' texts which become artefacts, in and of themselves, claiming a certain independence from the film, whilst at the same time maintaining dialogue with the film (Bakhtin), realized or not.